Effects of the transfer design on post-training performance in elearning - Cartaxo, M.; Simões, E. (INTED 2014 : conference proceedings, 2014)
Training in organizations is considered as a key factor for organizational development, and a tool for improving individual and organizational performance. However, training is only effective if knowledge and skills acquired during training are applied to the job, i.e., if the learning outcomes are transferred to workplace. Past research on the transfer of training has focused on various individual, group and organizational factors that before, during, and after training affect the probability that the acquired skills and knowledge are actually implemented in the workplace. Given the extant literature on the design of transfer, practitioners and training managers are prone to focus mostly on the training design itself and on the post-training procedures to enhance transfer. In order to contribute for studying the whole transfer processes in training activities, the main goal of this paper is to contribute for clarifying the effects of the design of learning transfer before and during eLearning training sessions. Results from an experimental study (N=115) show that the presence (vs. absence) of metacognitive orientations for transfer (design) before and during an e-learning. Session maximizes the effective transfer of learning. Specifically, participants who were instructed to mentally simulate a task in which they applied the skills learned in the training session performed better than those of the control group. This effect is moderated by perception of utility of training, in the sense that individuals who anticipated and mentally simulated task, and simultaneously perceived a greater utility of training, showed the highest performance. These results seem to highlight the importance of metacognitive dimension in the design of the transfer of learning, and especially of mental rehearsal of the use of skills and knowledge acquired in training.The practical implications of these results for enhancing the level of training transfer to the workplace are also discussed.